The Correlating Factors Aligned with Bullying Acts at Elementary Schools in Sumenep Regency - Sari, Tita Tanjung (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Recently, cases of bullying in the education sector have become increasingly prevalent in Indonesia. Bullying cannot be taken lightly as the emotional scars of infliction can damage a child's mental health, and it is not uncommon for victims of bullying to become bullies themselves in the future. This study aims to describe the correlating factors aligned with the bullying of elementary students in Sumenep Regency. Two hundred eighty-eight elementary school students from 14 schools participated in this research, and the data was analyzed using bivariate tests. The results of this study indicate that 68.1% of the respondents reported experiencing direct bullying, with 50% of those being boys. Additionally, 128 male students (44.4%) were reported as bullies. There is no significant relationship between gender and the experience of being bullied; every child has the potential to become a victim or perpetrator of bullying at school. Bullying is also closely related to academic achievement. The study does not expose any relationship between the experience of being bullied and the living situation of the students. Students feel sad and lacking in confidence when they are bullied, and they have tried to report this to relevant parties such as parents or teachers. However, the culture in Sumenep still considers bullying to be a common occurrence among children. Therefore, all parties must work together in addressing bullying, given the significant psychological impact it can have on children.